The extent of brachial plexus injury: an important factor in spinal accessory nerve to suprascapular nerve transfer outcomes. (2nd September 2020) - Rezzadeh, Kevin; Donnelly, Megan; Vieira, Dorice; Daar, David; Shah, Ajul; Hacquebord, Jacques
Abstract: Objective: The purpose of this study was to assess the association between extent of brachial plexus injury and shoulder abduction/external rotation outcomes after spinal accessory nerve (SAN) to suprascapular nerve (SSN) transfer. Methods: A systematic review of the literature was conducted according to PRISMA guidelines. Inclusion criteria were studies reporting outcomes on patients undergoing SAN to SSN nerve transfer. Patients were excluded for the following reasons: age under 18, nerve transfer for reanimation of the shoulder other than SAN to SSN, and less than 12 months of follow-up postoperatively. Pooled analysis was performed, and primary outcomes were Medical Research Council (MRC) score and range of motion (ROM) for shoulder abduction and external rotation. Univariate logistic regression analysis was used to assess the association between extent of brachial plexus injury and shoulder abduction/external rotation outcomes after SAN to SSN transfer. A multivariate logistic regression analysis model including age, injury to surgery interval, and extent of injury as factors was also created. Results: Univariate logistic regression analysis showed greater extent of injury to be a predictor of poorer shoulder abduction outcomes (OR: 0.502; 95% CI: 0.260–0.971, p  = 0.040). Multivariate logistic regression analysis confirmed this association (OR: 0.55; 95% CI: 0.236–0.877, p  = 0.019). Extent of injury was not significantly associated with external rotation outcomes on univariate analysis (OR: 0.435; 95% CI: 0.095–1.995, p  = 0.284) or multivariate analysis (OR: 0.445; 95% CI: 0.097–2.046, p  = 0.298). Age and injury to surgery interval were not significantly associated with postoperative outcomes. Conclusions: More extensive brachial plexus injuries are associated with inferior outcomes after SAN to SSN transfer. A potential explanation for this finding includes lost contribution of muscles from the shoulder girdle that receive innervation from outside of the upper brachial plexus. The relationship between extent of injury and postoperative outcomes is important to recognize when determining and discussing operative intervention with patients.